Application of statistical process control on a matrix card holder production - Syed Shaffizan, Saad Zenal Abidin (2008)
The thesis deals with durability assessment application of quality control in our production of card holder. The objective of this thesis is to let l know what is the exactly feature when production of card holder are made. The thesis describes the finite element analysis techniques to predict the fatigue life and identify the critical locations of the production. For material, using ABS that differ in other polypherine that also one of material that suitable to run this production. The 3D design of card holder was design by using Solid Work software. The strategy of calibration for specific measurement was established. After planning was organized, time to run Injection Molding to produce sample of card holder continuously in 3 phase, Injection Speed, Injection Pressure and Holding pressure. From the results, it is observed that the analysis using SPC tools mean process of production very incapable. By that, all factor and analysis were creating to remove all failure of process production.